(untitled) (Research, Society and Development, 2021)
The objective of this study was to evaluate the quality of life of elderly people with arterial hypertension in the ESF-São Benedito municipality of Poconé – MT. This work consists of an epidemiological, cross-sectional, quantitative study with a descriptive approach, through secondary data, referring to diagnosed hypertensive patients registered in the FHS. The results found were organized through the analysis of sixty questionnaires, with data from the registered elderly, which showed that 89.4% declared to be married 11.6% declared to be single. Regarding the condition of children, 98% declared having children. It was found that the highest percentage of elderly people, 67.6%, claimed to be the head of the family, followed by 32.9% who admitted to being the spouse or others. As for the data regarding the profile of habits and health, the results showed that 79.4% live in urban areas and these do not use alcoholic beverages and only 16.7% are smokers. Regarding the association with smoking, the study found similarity with the literature, as 16.7% of patients are associated with smoking. The results of the practice of physical activity, in this study, 36% perform some type of activity with predominant frequency and in 50% of the population three times or more a week. As for leisure habits, 100.0% of those evaluated stated that they perform some type of physical activity. It is considered that the purposes established for this study were achieved since it was possible to know part of the reality of the elderly registered by the HiperDia Program with an emphasis on their quality of life.